Peran Guru Agama Katolik Dalam Menguatkan Moderasi Beragama Di Sekolah - Jakomina Savera Mongi (Sepakat : Jurnal Pastoral Kateketik, 2023)
Religious moderation is an attitude that must be developed by the Indonesian people in maintaining unity and oneness. To strengthen this attitude, Catholic religion teachers have an important role, especially in schools. They can act as catechists, preachers, educators and pastoral service providers. In carrying out this task, they are saving the future of the Indonesian nation